Pengaruh Sistem Informasi SDM dan Disiplin Kerja terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening pada CV Multirejeki Selaras Kota Payakumbuh - Fauziyah Az-Zahra; Selvi Yona Sari; Nila Pratiwi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze the influence of HR Information Systems and Work Discipline on Employee Performance Through Job Satisfaction as an Intervening Variable at CV Multirejeki Selaras, Payakumbuh City. Data collection methods were through interviews and questionnaires. The population in this study was 40 employees. The data analysis method used was Structural Equation Modeling (SEM) using Partial Least Square (PLS). Based on the results of data analysis, it was found that HR Information Systems had a positive and significant effect on Job Satisfaction, Work Discipline had a positive and significant effect on Job Satisfaction, HR Information Systems had no and insignificant effect on Employee Performance, Work Discipline had no and insignificant effect on Employee Performance, Job Satisfaction had a positive and significant effect on Employee Performance, Job Satisfaction was able to mediate the effect of HR Information Systems on Employee Performance, Job Satisfaction was able to mediate the effect of Work Discipline on Employee Performance. The results of this study indicate that although the HR Information System and Work Discipline have a positive influence on Job Satisfaction, both do not have a direct influence on Employee Performance, but rather through the role of Job Satisfaction as a significant mediator.